Impact of the 13-valent Pneumococcal Conjugate Vaccine on Nasopharyngeal Carriage of Streptococcus pneumoniae Among Children Attending Group Daycare in Southeastern France. Issue 3 (March 2015) - Dunais, Brigitte; Bruno, Pascale; Touboul, Pia; Degand, Nicolas; Sakarovitch, Charlotte; Fontas, Eric; Haas, Hervé; Girard-Pipau, Fernand; Ruimy, Raymond; Pradier, Christian
Abstract : Regular surveys of pneumococcal nasopharyngeal carriage have been conducted among children attending daycare centers in Southeastern France from 1999 to 2012. We compared carriage rate, susceptibility patterns and serotype distribution in 2012, following implementation of the 13-valent pneumococcal conjugate vaccine, with findings from 5 previous surveys. Carriage rate was stable, antibiotic susceptibility improved and only serotype 19A persisted among vaccine-types.